A production process and casting of high compactness static pressure casting

By adding matte sand, manganese sand, carbon fiber and polyether modified silicone to the molded sand, and using synthetic resin, cyclodextrin and sodium bentonite as binders, the casting problem caused by high thermal expansion of quartz sand is solved and the casting is improved pass rate and production efficiency.

CN115351242BActive Publication Date: 2024-12-24SHIJIAZHUANG CITY HONGSEN SMELT CASTING CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202210871954.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2024-12-24
Estimated Expiration
2042-07-19

AI Technical Summary

Technical Problem

The high thermal expansion coefficient of quartz sand in existing molded sand molds leads to the castings being prone to warping, cracks, depressions, sand clamping and other problems during the casting process, which reduces the qualification rate and production efficiency of the castings.

Method used

Using specific ratios of sand formula, including shaved sand, manganese sand, diatomaceous earth, clay, mullite, carbon fiber, polyether modified silicone and binders, the quartz sand is reduced through wet and static pressure molding technology. The degree of expansion is improved and the mechanical properties and compatibility of the molded sand are improved by the addition of carbon fibers, and combined with synthetic resin, cyclodextrin and sodium bentonite as binders to optimize the bonding and molding of the molded sand.

Benefits of technology

The pass rate of castings is significantly improved, warping deformation and sand clamping are reduced, and the production efficiency of castings is improved, so that the pass rate of castings reaches 96-99%, and the molding sand moldability reaches 93.11% or above.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of static pressure casting, and relates to a production process of high-compactness static pressure castings and castings. The production process of high-compactness static pressure castings includes the following steps: sand mixing, static pressure molding, core making, casting, sand dropping, shot blasting, machining, paint curing, finished products and sand regeneration; the molding sand used in the sand mixing step is made of the following raw materials in percentage by weight: 23-27% of slag, 13-17% of manganese sand, 3-7% of diatomaceous earth, 3-7% of clay, 2.5-3.5% of mullite, and 0. 8-1.2%, binder 18-20%, polyether modified silicone 0.08-0.12%, water 3.5-3.8%, and the balance is quartz sand; the sand mixing step is as follows: mixing shale sand, manganese sand, diatomaceous earth, clay, mullite, carbon fiber, binder, polyether modified silicone, water and quartz sand; its process parameters are as follows: wet compressive strength 120-140kpa, air permeability ≥100, compaction rate 38±2%, moisture 3.5-3.8%; it has the advantage of improving the production efficiency of castings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of static pressure casting, and in particular to a production process and casting of a high-compactness static pressure casting. Background Art

[0002] Static pressure casting is a special casting process. The main principle is to maintain a certain pressure on the molten metal after casting to promote shrinkage compensation, improve the density of the casting, and thus obtain a casting with relatively high performance. Static pressure casting uses the airflow pre-compacting effect to initially compact the molding sand, and then uses the hydraulic pressure head to finally compact the molding sand.

[0003] Casting requires the use of molds, which are various molds and tools used in industrial production to obtain the desired products by injection molding, blow molding, extrusion, die casting or forging molding, smelting, stamping and other methods. The shape of the object is mainly processed by changing the physical state of the molded material, and the material of the casting mold can be sand, metal or even ceramic. Although the existing sand mold production process is mature, the amount of quartz sand in its mold composition is relatively high, and the thermal expansion coefficient of quartz sand is relatively large. Due to the high temperature during the casting process, the expansion of the sand easily causes the casting to warp, crack, dent, sand inclusion, etc., resulting in a large number of defective products, thereby reducing the production efficiency of the casting. Summary of the invention

[0004] In order to improve the qualified rate of castings and further improve the production efficiency of castings, the present application provides a production process and castings of high-compactness static pressure castings.

[0005] In a first aspect, the present application provides a production process for high-compactness static pressure castings, which adopts the following technical scheme: a production process for high-compactness static pressure castings, which comprises the following steps: sand mixing, static pressure molding, core making, casting, sand dropping, shot blasting, machining, paint curing, finished product and sand regeneration;

[0006] The molding sand used in the sand mixing step is prepared from the following raw materials in percentage by weight: 23-27% of slag, 13-17% of manganese sand, 3-7% of diatomaceous earth, 3-7% of clay, 2.5-3.5% of mullite, 0.8-1.2% of carbon fiber, 18-20% of binder, 0.08-0.12% of polyether modified silicone, 3.5-3.8% of water, and the balance is quartz sand;

[0007] The sand mixing steps are as follows:

[0008] Mix sintered sand, manganese sand, diatomaceous earth, clay, mullite, carbon fiber, binder, polyether modified silicone, water and quartz sand; the process parameters are as follows: wet compressive strength 120-140kpa, air permeability ≥100, compaction rate 38±2%, moisture 3.5-3.8%. By adopting the above technical scheme, the expansion coefficient of quartz sand is relatively large, and it expands when heated, which easily leads to over-size of castings. By adding sintered sand and manganese sand, this expansion degree can be reduced; adding carbon fiber, the excellent mechanical properties of carbon fiber can greatly improve the casting properties of molding sand; the added polyether modified silicone can make the compatibility between carbon fiber and the system better; thereby reducing the warping deformation, depression, sand inclusion and the like caused by excessive expansion of sand during the casting process, improving the qualified rate of castings, and thus improving the production efficiency of castings.

[0009] Preferably, the binder is made from the following raw materials in parts by weight: 3-5 parts of synthetic resin, 2-4 parts of cyclodextrin and 4-6 parts of sodium bentonite.

[0010] By adopting the above technical scheme, by compounding synthetic resin, cyclodextrin and sodium bentonite, it is found that when used as a molding sand binder, its bonding effect is stronger during casting, and its crushing index is higher after casting. Compared with using any one raw material alone, its crushing index and molding sand formability are better.

[0011] Preferably, the synthetic resin is phenolic resin or furan resin.

[0012] Preferably, the average length of the carbon fibers is 2-4 cm.

[0013] By adopting the above technical solution, within the length range of 2-4 cm, as the length of the carbon fiber gradually increases, the qualified rate of the castings gradually increases, which can reach between 96-99%, and at the same time, the molding sand formability gradually increases; but the molding sand crushing index gradually decreases. When the length of the carbon fiber is reduced to 1 cm, the qualified rate of the castings is reduced to 93%. Therefore, the addition of the carbon fiber and the length of the carbon fiber are important factors affecting the qualified rate of the castings, and the length of the carbon fiber is preferably 2-4 cm.

[0014] As a preference, the steps of core making are as follows:

[0015] The purchased coated sand is placed in a mold and core-made by a core-making machine; the parameters of the coated sand are as follows: gas evolution is less than 24 ml / g, loss on ignition is less than 4.5%, and bending resistance at room temperature is greater than 8 MPa.

[0016] As a preference: the casting steps are as follows:

[0017] After being heat-insulated and tempered, the molten iron from the blast furnace is poured into a ladle and then injected into the casting mouth of a casting mold. The molten iron is cooled and solidified to form a casting. The process parameters are as follows: smelting temperature 1450-1550℃, pouring temperature 1350-1420℃.

[0018] By adopting the above technical solution, under the process parameters, the probability of defective castings is low.

[0019] As a preference: the steps of spray paint curing are as follows:

[0020] The castings are sprayed with paint at a conveying speed of 0-2m / min. The painting is done manually and then sent to the curing channel for heating and curing. Electric heating hot air circulation is used and the curing temperature is 40-60℃. Both painting and curing are performed in a closed manner.

[0021] In a second aspect, the present application provides a high-compactness static pressure casting, which adopts the following technical solution:

[0022] A high-compactness static pressure casting, the casting is made by the production process of the high-compactness static pressure casting according to any one of claims 1 to 7

[0023] In summary, the present application includes at least one of the following beneficial technical effects:

[0024] 1. The expansion coefficient of quartz sand is large. When heated, it expands, which easily leads to oversize of castings. The addition of quartz sand and manganese sand can reduce this expansion degree. The addition of carbon fiber and its excellent mechanical properties can greatly improve the casting properties of the sand. The addition of polyether-modified silicone can make the compatibility between carbon fiber and the system better. This reduces the warping, dents, sand inclusions and other conditions caused by excessive expansion of sand during the casting process, improves the qualified rate of castings, and thus improves the production efficiency of castings.

[0025] 2. By compounding synthetic resin, cyclodextrin and sodium bentonite, it was found that when used as a molding sand binder, its bonding effect is stronger during casting, and its crushing index is higher after casting. Compared with using any one raw material alone, its crushing index and molding sand formability are better.

[0026] 3. The casting qualification rate of the production process of static pressure castings in this application is above 96%, and the highest can reach 99%; and the formability of the molding sand prepared in this application can reach 93.11% and above; the qualification rate of the production process of static pressure castings in this application is relatively high, and the formability of the molding sand is relatively good. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with the specific contents.

[0028] raw material

[0029] Among the raw materials used in the examples of the present application, the phenolic resin is 2130 phenolic resin; the model of the furan resin is 102; the cyclodextrin is β-cyclodextrin; the polyether-modified silicone is a polyether-modified silicone oil, and its model is ZS-204; the model of sodium bentonite is MZ-023; the model of diatomaceous earth is CD; and the remaining raw materials are common commercial products.

[0030] Example

[0031] Example 1

[0032] A production process for high-compactness static pressure castings, the specific steps of which are as follows:

[0033] (1) Sand mixing

[0034] The raw materials of the molding sand and the weight proportions of the raw materials are as follows: 23.4 parts of quartz sand, 25 parts of sintered sand, 5 parts of diatomaceous earth, 5 parts of clay, 2 parts of sodium bentonite, 3 parts of mullite, 1 part of carbon fiber, 19 parts of binder, 0.1 parts of polyether modified silicone and 3.5 parts of water are put into a sand mixer for mixing;

[0035] According to the requirements, the raw materials of the molding sand are put into a sand mixer for mixing according to the above weight proportions, wherein the process parameters are as follows: wet compressive strength 130 kpa, air permeability 100, compaction rate 38±2%, moisture 3.5%; the binder is prepared from synthetic resin, sodium bentonite and cyclodextrin, and is prepared according to the following weight proportions: 4 parts of synthetic resin, 5 parts of sodium bentonite, 3 parts of cyclodextrin; the synthetic resin is phenolic resin; the length of the carbon fiber is 2 cm.

[0036] (2) Static pressure molding

[0037] The mixed sand is molded by a static pressure molding machine, that is, the sand is preliminarily compacted by airflow pre-compacting, and then the sand is finally compacted by a hydraulic pressure head, and the multi-contact pressure head is provided with pressure by hydraulic pressure, and the pressure is fixed to obtain a mold;

[0038] (3) Core making

[0039] Put the coated sand into the mold, and make the core by the core making machine to obtain the casting mold; wherein the specifications of the coated sand are as follows: gas emission is 24ml / g, ignition loss is 4.5%, and bending resistance at room temperature is 8MPa;

[0040] (4) Casting

[0041] After being heat-insulated and tempered in an electric furnace, the molten iron from the blast furnace is poured into a ladle and then injected into the casting port of the mold obtained in step (3) on the casting line. The molten iron is cooled and solidified to form a casting. The process parameters are as follows: smelting temperature 1500°C, pouring temperature 1400°C;

[0042] (5) Falling sand

[0043] After the casting is cooled, the molding box is opened by the box opener, and the casting and the molding sand are separated by the sand falling machine, and the fallen molding sand is sent to the sand regeneration system;

[0044] (6) Shot blasting

[0045] The castings are cleaned and polished by shot blasting machines;

[0046] (7) Machining

[0047] The semi-finished products after shot blasting are then machined by lathe turning, drilling and tapping to meet the required shape and specifications. The machined castings are sent to the painting process for painting;

[0048] (8) Paint curing

[0049] The castings are sent to the paint spraying room for painting. The painting is carried out by continuous catenary conveying at a speed of 1m / min. A scissor lift is used to assist in loading and unloading of parts. The painting is carried out manually. After painting, the castings are sent to the curing channel for heating and curing. Electric heating hot air circulation is used. The curing temperature is 50°C. The paint spraying room and curing room are operated in a closed manner. The exhaust gas from the paint spraying is treated by the water curtain paint mist treatment system + demister in the paint spraying room, and then enters the activated carbon adsorption and desorption + catalytic combustion treatment together with the curing exhaust gas, and finally discharged through a 15m high exhaust pipe;

[0050] (9) Finished product

[0051] Finished products that pass the inspection are transported to the warehouse for storage;

[0052] (10) Sand regeneration

[0053] The molding sand produced by the falling sand is collected and put into the sand processing system to remove impurities, sand lumps, large iron beans and flash, etc. in the sand, and then the sand is regenerated by the sand regeneration system; among them, when the molding sand is crushed, the crushing index (j) is 90%.

[0054] Example 2

[0055] A production process for high-compactness static pressure castings, which is different from Example 1 in that the length of the carbon fiber is 3 cm, and the remaining steps are the same as Example 1; wherein, when the molding sand is crushed, the crushing index (j) is 88%.

[0056] Example 3

[0057] A production process for high-compactness static pressure castings, which is different from Example 1 in that the length of its carbon fiber is 4 cm, and the remaining steps are the same as Example 1; wherein, when the molding sand is crushed, the crushing index (j) is 85%.

[0058] Comparative Example

[0059] Comparative Example 1

[0060] A production process for high-compactness static pressure castings, which is different from Example 1 in that its binder is a synthetic resin of equal mass, and the remaining steps are the same as Example 1; wherein, when the molding sand is crushed, the crushing index (j) is 78%.

[0061] Comparative Example 2

[0062] A production process for high-compactness static pressure castings, which is different from Example 1 in that its binder is cyclodextrin of equal mass, and the remaining steps are the same as Example 1; wherein, when the molding sand is crushed, the crushing index (j) is 79%.

[0063] Comparative Example 3

[0064] A production process for high-compactness static pressure castings, which is different from Example 1 in that its binder is sodium bentonite of equal mass, and the remaining steps are the same as Example 1; wherein, when the molding sand is crushed, the crushing index (j) is 79%.

[0065] Comparative Example 4

[0066] A production process for a high-compactness static pressure casting, which is different from Example 1 in that the average length of its carbon fiber is 1 cm, and the remaining steps are the same as Example 1.

[0067] Comparative Example 5

[0068] A production process for high-compactness static pressure castings, which is different from Example 1 in that the polyether-modified silicone is replaced by an equal amount of silane coupling agent, the silane coupling agent is KH550, and the remaining steps are the same as Example 1.

[0069] Performance testing

[0070] Detection method / test method

[0071] Taking the casting of the flywheel housing as an example, 100 pieces of high-compactness static pressure castings were produced according to the production process of Examples 1-3 and Comparative Examples 1-5, and then tested according to the following testing method. The test results are shown in Table 1.

[0072] Any of the following situations will be considered unqualified: cracks in the casting, fire in the casting, out-of-tolerance casting dimensions (warping, dents, roughness, etc.), etc.

[0073] Table 1 Test data of Examples 1-3 and Comparative Examples 1-5

[0074] Sand forming properties (%) Casting qualification rate (%) Example 1 93.11 96 Example 2 93.14 98 Example 3 93.15 99 Comparative Example 1 87.32 91 Comparative Example 2 86.78 90 Comparative Example 3 86.69 90 Comparative Example 4 92.77 93 Comparative Example 5 91.13 92

[0075] It can be seen from Examples 1-3 and Comparative Examples 1-5, as well as the test data in Table 1, that the casting qualification rate of the production process of the static pressure castings of the present application is above 96%, and can reach up to 99% at the highest; and the formability of the molding sand prepared in the present application can reach 93.11% and above; indicating that the production process of the static pressure castings of the present application has a high qualification rate, and the moldability of the molding sand is better.

[0076] It can be seen from the test data of Examples 1-3 that within the length range of 2-4 cm, as the length of the carbon fiber gradually increases, the qualified rate of the castings gradually increases, and the molding sand formability gradually increases; but the molding sand crushing index gradually decreases. Combined with Comparative Example 4, when the length of the carbon fiber is reduced to 1 cm, the qualified rate of the castings is reduced to 93%. Therefore, the addition of the carbon fiber and the length of the carbon fiber are important factors affecting the qualified rate of the castings, and the length of the carbon fiber is preferably 2-4 cm.

[0077] It can be seen from the test data of Example 1 and Comparative Examples 1-3 that the three raw materials in the binder, synthetic resin, cyclodextrin and sodium bentonite, have a synergistic effect. When the three are added together, the molding sand has a higher formability and a higher crushing index.

[0078] It can be seen from the test data of Example 1 and Comparative Example 5 that when the polyether-modified silicone is replaced by a silane coupling agent, the molding sand formability thereof is reduced, and the qualified rate is gradually reduced significantly.

[0079] The above-mentioned specific implementation examples are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A production process for high-compactness static pressure castings, characterized in that: It includes the following steps: sand mixing, static pressure molding, core making, casting, sand dropping, shot blasting, machining, painting and curing, and the finished products that have passed the inspection are transported to the warehouse for storage and sand regeneration; The molding sand used in the sand mixing step is prepared from the following raw materials in percentage by weight: 23-27% zircon sand, 13-17% manganese sand, 3-7% diatomaceous earth, 3-7% clay, 2.5-3.5% mullite, 0.8-1.2% carbon fiber, 18-20% binder, 0.08-0.12% polyether modified silicone, 3.5-3.8% water, and the balance is quartz sand; The sand mixing steps are as follows: Mix zircon sand, manganese sand, diatomaceous earth, clay, mullite, carbon fiber, binder, polyether modified silicone, water and quartz sand; the process parameters are as follows: wet compression strength 120-140kpa, air permeability ≥100, compaction rate 38±2%, moisture 3.5-3.8%; The binder is prepared from the following raw materials in parts by weight: 3-5 parts of synthetic resin, 2-4 parts of cyclodextrin and 4-6 parts of sodium bentonite; The synthetic resin is a phenolic resin or a furan resin; The average length of the carbon fiber is 2-4 cm; The steps of core making are as follows: The coated sand is placed in a mold and core-made by a core-making machine; the parameters of the coated sand are as follows: gas evolution is less than 24 ml / g, loss on ignition is less than 4.5%, and bending resistance at room temperature is greater than 8 MPa.

2. The production process of a high-compactness static pressure casting according to claim 1, characterized in that: The casting steps are as follows: After being heat-insulated and tempered, the molten iron from the blast furnace is poured into a ladle and then injected into the casting mouth of a casting mold. The molten iron is cooled and solidified to form a casting. The process parameters are as follows: smelting temperature 1450-1550℃, pouring temperature 1350-1420℃.

3. The production process of a high-compactness static pressure casting according to claim 1, characterized in that: The steps of spray paint curing are as follows: The castings are sprayed with paint at a conveying speed of 0-2m / min. The painting is done manually and then sent to the curing channel for heating and curing. Electric heating hot air circulation is used and the curing temperature is 40-60℃. Both painting and curing are performed in a closed manner.

4. A high compactness static pressure casting, characterized in that: The casting is produced by the production process of high-compactness static pressure castings according to any one of claims 1-3.

Citation Information

Patent Citations

  • Molding sand for automatic molding and preparation method thereof

    CN104493071A

  • Precoated sand appropriate for manufacturing of thin-walled core sand and preparation method of precoated sand

    CN104841861A

  • Well-formed low-expansion cast precoated sand and preparation method thereof

    CN104841870A

  • Core sand for automobile engine casting and preparation method of core sand

    CN106111884A

  • Method for producing high manganese steel track plate by static-pressure modeling casting molding process

    CN106238668A